A comparison of flea control measurement methods for tracking flea populations in highly infested private residences in Tampa FL, following topical treatment of pets with FRONTLINE® Plus (Fipronil/(S)-Methoprene) - Dryden, Michael W.; Carithers, Doug; McBride, Amy; Riggs, Breanne; Smith, Lindsey; Davenport, Jacob; Smith, Victorene E.; Payne, Patricia; Gross, Sheila J. (My University, 2012)
The efficacy of fibronil/(S)-methoprene (FRONTLINE® Plus, Merial Limited, Duluth GA, USA) for household flea control was assessed against existing natural flea populations in homes in Tampa, Florida. Twenty-seven households fulfilled requirements for inclusion into and completed this non-randomized, multiple site (household), prospective field study. The study duration was 60 days, with all household dogs and cats treated with FRONTLINE® Plus on day 0 and day 28-30. Three separate household flea-control assessment methods were used in this study, and each was evaluated to determine its ability to effectively gauge household flea control of natural flea populations in homes. The three methods of assessing household flea control were: 1) Counting fleas captured in intermittent-light environmental flea emergence traps placed in heavily infested areas of the house. 2) Examination of the sex ratios of the fleas captured in the intermittent-light environmental flea emergence traps, and 3) assessing pet flea burdens, as has been typically done historically. Our findings in this study demonstrated that in field situations, the most accurate measure of household flea control trends is determined by comparing counts, over time, of newly emerged (unfed) fleas caught in intermittent-light environmental flea emergence traps. This study also verified that determining sex ratios of the newly emerged trapped fleas provides the best indication of the immediate population trend in flea-infested households. In household studies such as this, when household pets have access to the outdoor environment, this study clearly demonstrated that on-animal flea counts can be inconsistent and provides the least reliable indicator available for measuring suppression of household flea infestations. These findings demonstrated that in field situations FRONTLINE® Plus provided effective flea control, as assessed by the significant decline in flea emergence from the contaminated household.
Keywords: Ctenocephalides felis; Fleas; Emergent fleas; Flea sex ratio; Dog; Cat; Household study; Flea trap counts; On-animal flea counts